Manajemen Komunikasi Pendidikan Multikultural menuju Pendidikan Damai dan Toleransi - Mustaqim Mustaqim (Universitas Merdeka Malang, 2020)
The focus of this research is on management of educational communication in enhancing the attitude of multiculturalism, both communication management at the class and faculty level. This research approach is qualitative with descriptive analytic type, while the techniques of collecting data are observation, interview and documentation as well as a closed questionnaire specifically for multiculturalism attitude data. Data analysis techniques using Milles and Huberman patterns, namely data reduction, data presentation and conclusion drawing, specifically the data of multiculturalism attitude analyzed quantitative descriptive. The results of this study found that multicultural education communication management strategies include the educational system, communicator credibility, communication processes in learning / lectures, educational institution culture, content of teaching materials, communicant attitudes, multiculturalism values, and the involvement of all social education environments. 78% have a multicultural attitude towards the civitas and alumni in supporting the application of multiculturalism values. This is supported by internal factors, namely educational communicators, messages in the form of lecture materials related to multiculturalism, culture or campus climate which intersect with multiculturalism. While external factors, including: Balinese culture and habits of interaction between Balinese with foreign cultures.Keywords: Communication Management, Education, MulticulturalDOI: https://doi.org/10.26905/nomosleca.v6i1.4037